2023
DOI: 10.3389/fendo.2023.1234256
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the alarming rise of diabetic ketoacidosis during COVID-19 pandemic: a pioneer African study and review of literature

Abstract: IntroductionReports around the world indicate that COVID-19 pandemic may be contributing to an increase in the incidence of new onset diabetic ketoacidosis (DKA). This has yet to be studied in Africa. We aimed to compare the incidence trend of new onset DKA before and during the COVID-19 pandemic, with a focus on the type of diabetes mellitus (DM).Materials and methodsThis was a cross sectional analytical study, over a 4-year period, between March 2018 until February 2022 conducted in the referral center: diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…50 In a study from Tunisia, that investigated the incidence of new onset DKA between March 2018 and February 2022, investigators reported a 48% increase during the pandemic with the frequency of T1D and T2D rising by 50% and 40% respectively. 51 By contrast, a study from Belgium found that the prevalence of anti-SARS-CoV-2 antibodies in people of the same age with new-onset T1D was similar to that found in children without diabetes. 52 Nevertheless, retrospective data from 27,292,879 patients from a national US database (Cerner Real-World Data) showed that COVID-19 diagnosis was associated with a significantly increased risk of new-onset T1D with specific ethnicities being more susceptible.…”
Section: Discussionmentioning
confidence: 87%
“…50 In a study from Tunisia, that investigated the incidence of new onset DKA between March 2018 and February 2022, investigators reported a 48% increase during the pandemic with the frequency of T1D and T2D rising by 50% and 40% respectively. 51 By contrast, a study from Belgium found that the prevalence of anti-SARS-CoV-2 antibodies in people of the same age with new-onset T1D was similar to that found in children without diabetes. 52 Nevertheless, retrospective data from 27,292,879 patients from a national US database (Cerner Real-World Data) showed that COVID-19 diagnosis was associated with a significantly increased risk of new-onset T1D with specific ethnicities being more susceptible.…”
Section: Discussionmentioning
confidence: 87%
“…Secondly, the virus itself had been shown in the literature to be responsible for triggering inflammatory and autoimmune diseases. 24 , 25 The expression of ACE2 in the hypothalamus was confirmed, making it a probable target for SARS-CoV-2. 26 A COVID-19-infected patient may present with panhypopituitarism or pituitary apoplexy.…”
Section: Discussionmentioning
confidence: 87%
“…During the pandemic, while emergency room visits decreased, an increasing number of admissions to hospitals due to DKA have been reported from different parts of the world [6,7,[15][16][17][18][19]. The impact of the pandemic on the incidence and seasonal variability of T1DM continues to be investigated with different results from many regions [9,10,[20][21][22][23][24][25][26][27]. In our study, in which the effect of the pandemic process on the diagnosis and presentation of T1DM was evaluated, it was observed that they presented with a more severe clinical picture during the pandemic.…”
Section: Discussionmentioning
confidence: 99%